Conference Photos - Plotkin, Eugene; Mikaelian, Vahagn (Armenian Journal of Mathematics, 2016)
The First International Algebra and Geometry Conference in Armenia 16-20 May, 2007, Yerevan. Conference Photos by Eugene Plotkin and Vahagn H. Mikaelian